Management of Jeerna Vataja Kasa (Allergic Bronchitis) in Chronic Constipation Patient- A case report - Vasant Patil; Anuja Daga (Journal of Ayurveda and Holistic Medicine (JAHM), 2026)
Background: Kasa (cough) is the Vata-Kapha Pradhana Vyadhi which is caused by excessive intake of Katu (pungent), Amla (sour), Lavana (salty), Ruksha (dry), Sheeta (cold), Guru (heavy), Snigdha (oily) food along with Divaswapna (day sleep), Ratri Jagarana(night vigil). Due to Nidana, Vata gets aggravated causing Shushka Kasa etc Lakshana leading to Vataja Kasa. Allergic bronchitis is characterized by inflammation of bronchial tubes resulting in cough, chest pain etc. Clinical Findings: A 46 years old female patient with known case of HTN presented complaints of Shushka Kasa (dry cough) persisting from past 3 months aggravated during day time associated with Malavarodha (Constipation) since 15 years and Appetite (reduced appetite) since 2days. Patient was intended to treat with Ayurveda line of treatment for 1month and got 90% improvement but again symptoms aggravated. So, consulted pulmonologist and was treated with steroid therapy for 5days. Complaints aggravated since 2days, hence she opted for Ayurvedic management where she was diagnosed with Jeerna Vataja Kasa with chronic constipation and a structured ayurvedic treatment was adopted. Interventions: Treatment was planned according to classical approach which included Shamana Aushada (oral medication) and Shamananga Snehapana (internal oleation), Pathyapthya, Yoga and Mudra This intervention was administered over a period 4 months 4days with regular follow ups. Outcome: After 4months 4days, clinical assessment showed marked improvement in symptoms i.e. Bronchitis severity score (BSS-5 reduced to 0),Leicester cough questionnaire (LCQ-9.89 improved to 19.75) and Wexner constipation score reduced (from score 9 to score 1). Conclusion: A three months chronic case of Kasa and chronic constipation of over 15years was successfully managed highlighting the potential of whole-system Ayurveda in offering sustainable relief and management for chronic disorders unresponsive to modern medicine.